Effects of simulated warming and litter removal on structure and function of semi-humid alpine grassland in the Qinghai-Tibet Plateau - Xue, Guomin; Tian, Lihua; Zhao, Jingxue (Frontiers in Plant Science, 2025)
Climate warming and human activities are modifying plant litter inputs in alpine grasslands, which is predicted to affect ecosystem structure and function. However, the effects of plant litter removal and warming as well as the combined impacts on the ecological functions of alpine grasslands are not well understood. A field experiment was conducted to investigate the effects of experimental warming, litter removal, and their interaction on ecosystem multifunctionality (EMF) of alpine grasslands. Our results demonstrated a significant decrease in plant diversity (p < 0.05) and vegetation cover (p < 0.01) under experimental warming treatment, whereas the richness index (R) and belowground biomass (BGB) significantly increased under litter removal treatment (p < 0.05). The interaction effect of experimental warming and litter removal results in a neutralizing effect on the ecological functions in alpine grasslands. Meanwhile, the EMF tended to increase under all treatments of experimental warming, litter removal, and experimental warming-litter removal. However, there are differences in the response of aboveground and belowground multifunctionality to experimental warming and litter removal. The aboveground ecosystem multifunctionality (AEMF) showed a decreasing trend, while belowground ecosystem multifunctionality (BEMF) increased significantly (p < 0.01) under the experimental warming treatment. In contrast, AEMF and BEMF showed an increasing trend in litter removal treatment. In addition, the study found that litter removal could alleviate the negative effect of experimental warming on multiple ecological functions. These research findings can serve as a reference for maintaining ecosystem functions in alpine grasslands under climate change conditions and provide effective measures to enhance the capacity of grassland ecosystems to respond to climate change. The application of appropriate litter management measures and other nature-based solutions (NbS) to improve ecosystem functions, aiming to adopt sustainable approaches to address environmental challenges, holds significant importance for ecological conservation.